2019
DOI: 10.1164/rccm.201808-1493oc
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Atomoxetine and Oxybutynin Greatly Reduces Obstructive Sleep Apnea Severity. A Randomized, Placebo-controlled, Double-Blind Crossover Trial

Abstract: Rationale: There is currently no effective pharmacological treatment for obstructive sleep apnea (OSA). Recent investigations indicate that drugs with noradrenergic and antimuscarinic effects improve genioglossus muscle activity and upper airway patency during sleep. Objectives: We aimed to determine the effects of the combination of a norepinephrine reuptake inhibitor (atomoxetine) and an antimuscarinic (oxybutynin) on OSA severity (apnea-hypopnea index [AHI]; primary outcome) and genioglossus responsiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(184 citation statements)
references
References 34 publications
10
167
5
2
Order By: Relevance
“…115 Nonetheless, a recently completed trial investigating the impact of atomoxetine, a norepinephrine reuptake inhibitor, and oxybutynin, an antimuscarinic drug, on OSA showed dramatic improvements in the apnea-hypopnea index. 116 The relevance of the currently investigated drugs in the pregnant population is unclear because upper airway function, ventilatory control, and arousal physiology may all be different in this population due to the effect of significantly elevated levels of sex hormones 4 and other pregnancy-specific factors. Hence, there is a need to better understand pregnancy-specific physiology of upper airway and ventilatory control prior to attempting the use of pharmacotherapy in this population.…”
Section: Pharmacologic Interventions In Osamentioning
confidence: 99%
“…115 Nonetheless, a recently completed trial investigating the impact of atomoxetine, a norepinephrine reuptake inhibitor, and oxybutynin, an antimuscarinic drug, on OSA showed dramatic improvements in the apnea-hypopnea index. 116 The relevance of the currently investigated drugs in the pregnant population is unclear because upper airway function, ventilatory control, and arousal physiology may all be different in this population due to the effect of significantly elevated levels of sex hormones 4 and other pregnancy-specific factors. Hence, there is a need to better understand pregnancy-specific physiology of upper airway and ventilatory control prior to attempting the use of pharmacotherapy in this population.…”
Section: Pharmacologic Interventions In Osamentioning
confidence: 99%
“…Further data are clearly required to assess hard outcomes before widespread use of wake‐promoting pharmacotherapy can be strongly advocated. In addition, there are no studies to date comparing the different wake‐promoting agents in sleepy OSA patients.Regarding therapeutic pharmacotherapy for OSA, a recent study showed potential benefits of the combination of atomoxetine, a selective norepinephrine reuptake inhibitor, plus oxybutynin, an anti‐muscarinic, for the treatment of OSA . Based on the premise that norepinephrine drive is central to pharyngeal muscle tone and muscarinic activity to rapid eye movement (REM) sleep‐related pharyngeal tone, the combination of atomoxetine and oxybutynin was hypothesized to cause an increase in genioglossus activity and reduce OSA severity.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%
“…Taken together with the data from Horner's lab in sleeping rats, the study provides credible evidence that noradrenergic drugs may be useful in OSA. These experiments laid the foundation for a recent human clinical trial utilizing a combination of the noradrenergic agonist, atomoxitine, and a muscarinic blocker, oxybutinine [77]. Nevertheless, both classes of drugs have significant systemic adverse effects on cardiovascular, gastrointestinal, and urogenital systems, limiting their clinical use.…”
Section: Animal Models Of Neuromuscular Response: Emg Outcomesmentioning
confidence: 99%